Ms. Marvel. Vol. 7, Damage per second - Wilson, G. Willow, 1982- (Marvel now!, 2017)
"Civil War II is behind her, and a brand new chapter for Kamala Khan is about to begin! But it's lonely out there for a super hero when her loved ones no longer have her back. It's time for Kamala to find out exactly who she is when she's on her own. And Kamala's home life, costumed life and online life will converge when a member of her World of Battlecraft guild reveals he's discovered her secret identity!" -- page 4 of cover.